Authorship And Collaborative Pattern In The Field Of Nephrology: A Scientometric Study (Journal of Pharmaceutical Negative Results, 2022)
The purpose of this study was to measure the number of contributions and highlight the contributions made by the researchers in the field of Nephrology and published on the Web of Science database during 2012-2021 using scientometric analysis. The data was interpreted by using software such as Bibexcel and Vosviewer and tabulated using MS Excel. The results indicated that 7539 papers were published during 2012-2021 and the highest number of publications, 1166 (15.4%) was produced in 2020. For ten years journals were the major channel of communication used by researchers. The trends in multi-authored papers have tremendously increased (90.16%) compared to (9.84%) single-authored papers. The degrees of collaboration (0.90%) are noted significantly and the highest number of papers 967 (12.8%) was contributed by the collaboration of two authors. It also noted that the value of the highest degree of collaboration was (0.94%) in 2021. The publication behavior of researchers shows that they are highly selective in publishing the research results in specialized articles. The collaborative index (6.47%) was produced in 2021 and also, collaborative co-efficient papers have increased (0.75%) in 2021.